2013
DOI: 10.3233/jbr-130043
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds profile of strawberry fruits of Charlotte cultivar

Abstract: The profile of phenolic compounds in strawberry fruits varies significantly among cultivars. High performance liquid chromatography with diode array detection coupled to electrospray ionization mass spectrometric detection with positive and negative modes of ionization was employed to identify phenolic compounds in extract of strawberries from Charlotte cultivar. This is the first time phenolic profile of Charlotte cultivar has been characterized. The fruits contained phenolics belonging to six groups: anthocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…ents and corresponded with results reported by other researchers (Sun et al 2014). The study conducted by Tulipani et al (2008) and Kosińska et al (2013) demonstrated various contents of polyphenolic compounds in strawberries, depending on their variety (from approx. 5.0 to more than 8.0 g GAE 100 g -1 d.m).…”
Section: Resultssupporting
confidence: 90%
“…ents and corresponded with results reported by other researchers (Sun et al 2014). The study conducted by Tulipani et al (2008) and Kosińska et al (2013) demonstrated various contents of polyphenolic compounds in strawberries, depending on their variety (from approx. 5.0 to more than 8.0 g GAE 100 g -1 d.m).…”
Section: Resultssupporting
confidence: 90%
“…Deoxyhexoses are a class of six-carbon monosaccharides that have had one or more of their hydroxyl groups replaced with hydrogen atoms and include rhamnose, arabinose, quinovose and fucose. Aaby et al 9 reported the presence of ellagic acid deoxyhexoside in the ripe fruits of the cultivated strawberry, with subsequent studies also reporting the presence of the compound in strawberry fruit [10][11][12]30 . Far less is known about the biosynthesis of ellagitannins than about the biosynthesis of phenylpropanoids, flavonoids, and anthocyanins.…”
Section: Genetic Control Of Ellagic Acid Deoxyhexoside Productionmentioning
confidence: 98%
“…Gallic acid (10), 1-O-glucoside (9), and 1,2,3,4,6-penta-O-galloylglucose (67) were identified by comparison with reference standards. Gallic acid derivatives and gallotannins are not typical phenolics of Fragaria genus, but gallic acid is a metabolite found in F. ananassa [2] and compound 67 is detected in F. ananassa fruits [35] and F. vesca leaves [36]. .…”
Section: Gallic Acid Derivativesmentioning
confidence: 99%